2012
DOI: 10.1177/0959651812459303
|View full text |Cite
|
Sign up to set email alerts
|

Accurate pressure control of a pneumatic actuator with a novel pulse width modulation–sliding mode controller using a fast switching On/Off valve

Abstract: Pressure control of a pneumatic actuator using fast switching On/Off valves continues to remain a major challenge for researchers. This article proposes a novel pulse width modulation–sliding mode controller that improves pressure tracking of pneumatic actuators. First, a comprehensive mathematical model of the pneumatic system was developed that consists of several submodels. The model comprises pressure and temperature equations describing the thermodynamic process inside the pneumatic chamber, an orifice fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…where V is the volume composed of the air passage and the air cylinder chamber. By substituting equation (8) and (9) into equation (11), the dynamic differential equation of air chamber pressure in the process of filling can be obtained: (12) P = dp dt (13) Obviously, the values of upstream and downstream pressure vary with the process of filling and exhausting for the air cylinder. During filling process, the pressure in the high pressure supply should be viewed as the upstream pressure, whereas the pressure in the air cylinder is viewed as the downstream pressure and vice versa during the exhausting process.…”
Section: B Mathematical Model Of Braking Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…where V is the volume composed of the air passage and the air cylinder chamber. By substituting equation (8) and (9) into equation (11), the dynamic differential equation of air chamber pressure in the process of filling can be obtained: (12) P = dp dt (13) Obviously, the values of upstream and downstream pressure vary with the process of filling and exhausting for the air cylinder. During filling process, the pressure in the high pressure supply should be viewed as the upstream pressure, whereas the pressure in the air cylinder is viewed as the downstream pressure and vice versa during the exhausting process.…”
Section: B Mathematical Model Of Braking Systemmentioning
confidence: 99%
“…To enhance the working performance of the on-off solenoid valve system further, some comprehensive researches on control algorithms have been carried out by researchers globally and some fruitful achievements have been achieved. Hejrati and Najafi [9] proposed a new pulse width modulation with sliding mode controller for pressure tracking, and some experiments were implemented and demonstrated that pressure control performance of pneumatic actuators had a significant improvement compared to other controllers from the literatures. Lv et al [6], [10] presented a pressuredifferent-limiting modulation control method for regenerative braking system and obtained a linear hydraulic pressure control performance between coil current and pressure difference across the tested valves.…”
Section: Introductionmentioning
confidence: 99%
“…This equivalently continuous technique has been proven effective in controlling other pneumatic systems. 6,14 Moreover, the valves in an actual electropneumatic brake have delay times when they are being switched on or off. That is to say, if the switched on and off delay times of a valve are defined as t on and t off and the duty-cycle of the PWM control signal is less than t on =t PWM (t PWM is the PWM period), then the actual duty-cycle of the valve would be 0.…”
Section: Order-reduced Modelmentioning
confidence: 99%
“…Discontinuity-the discontinuity nature of On/Off valves, used to regulate pneumatic pressures in the brake, makes the brake model discontinuous. 5,6 Over the years, researchers have proposed knowledge-based controllers based on fuzzy logic control method. 7,8 Although developing a knowledgebased controller does not require an explicit mathematical model of the plant, it requires knowledge or experience from an expert (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation